Exploring public opinion on health effects of prepared dishes in China through social media comments - Shu, Tao; Yang, Han; Lin, Ling; Chen, Jian; Zhou, Jixian; Wang, Jun (Frontiers in Public Health, 2024)
In the 2020s, with the government and Industrial capital, China’s prepared dishes industry experienced rapid growth. Nevertheless, this swift expansion has elicited varied public opinions, particularly concerning the potential health effects of prepared dishes. This study aims to gather and analyze comments from social media on prepared dishes using machine learning techniques to ascertain the perspectives of the Chinese populace on the health implications of consuming prepared dishes. At the outset, the Social media comments data underwent a preprocessing fitting for analysis. The subsequent steps involved conducting sentiment analysis and utilizing the BERTopic model for topic clustering to identify the primary concerns of the public regarding the impact of prepared dishes on health. The final phase of the study encompassed a comparative analysis of changes in public sentiment focus across different time frames, revealing a dynamic perception related to the health implications of prepared dishes. 200,993 clean comments gathered from various platforms from mid-July 2022 to the end of March 2024 were assessed for sentiment, revealing that more than 64% exhibited negative emotions. Subsequent topic clustering using the BERTopic model identified that 11 of the top 50 topics were related to public health concerns. These topics primarily scrutinized the safety of prepared dish production processes, raw materials, packaging materials, additives, and the right to informed consumption across different contexts. Notably, the most pronounced public opposition emerged regarding introducing prepared dishes into primary and secondary school canteens, with criticisms directed at the negligence of educational authorities and the ethics of manufacturers. The findings of this study indicate that more than 60% of the Chinese public maintains a negative perception of prepared dishes, particularly concerning their health implications for adolescents. Chinese individuals display considerable sensitivity and intense reactions to news and events related to prepared dishes. Consequently, the study recommends that manufacturers should proactively enhance production processes and service quality, as well as increase transparency in public communications to improve corporate image and people's acceptance. Additionally, media organizations and governmental bodies must intensify their supervisory and regulatory efforts, thereby fostering the healthy development of the prepared dishes industry in China.